1986
DOI: 10.1111/j.1399-0004.1986.tb01242.x
|View full text |Cite
|
Sign up to set email alerts
|

Long term survival of a patient with the cerebro‐hepato‐renal (Zellweger) syndrome

Abstract: A 13‐year‐old girl with severe mental retardation, tapetoretinal degeneration, an extinguished electroretinogram and sensoneurinal hearing loss is described. In early life the diagnosis of Zellweger (cerebro‐hepato‐renal) syndrome was considered because of hypotonia, craniofacial dysmorphia, abnormal liver functions and pipecolic aciduria. Biochemical studies in fibroblasts from the patient revealed a general peroxisomal dysfunction comparable to the findings in Zellweger Syndrome. As the clinical presentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…There were 10 cohort studies [ 8 , 16 , 29 , 42 , 51 , 99 , 117 , 118 , 119 , 120 ] and 31 case studies [ 6 , 11 , 15 , 26 , 32 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ] that described 124 patients with mild ZSD (80 from cohort studies, 36 from case studies). In the cohort studies, a seizure disorder was reported in 15.9% of patients (out of 63 total), hypotonia was present in 50.0% of patients (out of 42 patients total), reduced mobility was reported in 35.7% of patients (out of 70 patients total), feeding difficulties were reported in 14.8% of patients (out of 54 patients total), abnormal liver function or structure was reported in 54.3% of patients (out of 70 patients total), adrenal insufficiency was reported in 11.8% of patients (out of 34 patients total), and hearing loss was present in 52.0% of patients (out of 75% patients total) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were 10 cohort studies [ 8 , 16 , 29 , 42 , 51 , 99 , 117 , 118 , 119 , 120 ] and 31 case studies [ 6 , 11 , 15 , 26 , 32 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ] that described 124 patients with mild ZSD (80 from cohort studies, 36 from case studies). In the cohort studies, a seizure disorder was reported in 15.9% of patients (out of 63 total), hypotonia was present in 50.0% of patients (out of 42 patients total), reduced mobility was reported in 35.7% of patients (out of 70 patients total), feeding difficulties were reported in 14.8% of patients (out of 54 patients total), abnormal liver function or structure was reported in 54.3% of patients (out of 70 patients total), adrenal insufficiency was reported in 11.8% of patients (out of 34 patients total), and hearing loss was present in 52.0% of patients (out of 75% patients total) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%